Diverse communities: The problem with social capital - Arneil, Barbara (Cambridge University, 2013)
Diverse Communities is a critique of Robert Putnam's social capital thesis, re-examined from the perspective of women and cultural minorities in America over the last century. Barbara Arneil argues that the idyllic communities of the past were less positive than Putnam envisions and that the current 'collapse' in participation is better understood as change rather than decline. Arneil suggests that the changes in American civil society in the last half century are not so much the result of generational change or television as the unleashing of powerful economic, social and cultural forces that, despite leading to division and distrust within American society, also contributed to greater justice for women and cultural minorities. She concludes by proposing that the lessons learned from this fuller history of American civil society provide the normative foundation to enumerate the principles of justice by which diverse communities might be governed in the twenty-first century.